Can copper-based substrates be used to protect hatcheries from invasion by the New Zealand mudsnail? - Hoyer, Scott, author; Myrick, Christopher A., advisor; Clements, William H. (William Henry), 1954-, committee member; Kondratieff, B. C. (Boris C.), committee member (Colorado State University. Libraries, 2011)
Aquaculture facilities throughout North America are at risk of invasion by the New Zealand mudsnail (Potamopyrgus antipodarum). Mudsnails can enter facilities in several ways including by crawling through effluent pipes. There is evidence to suggest that lining the insides of these pipes with copper-based substrates to create a contact deterrent could reduce the risk of mudsnail invasion. However, before copper-based deterrents can be recommended for wide-scale use, it is important that we understand how these materials perform across the range of physicochemical conditions common to hatcheries. The goal of this project was to evaluate the relative ability of four types of copper-based materials (copper sheet; SC (0.323 mm, 99.9% pure), copper mesh; MC (6.3 opening/cm, 99% pure), copper-based ablative anti-fouling paint; AP (Vivid Anti-fouling Paint, 25% cuprous thiocyanate as the active ingredient), and copper-based non-ablative anti-fouling paint; NP (Sealife 1000, 39% cuprous oxide as the active ingredient)) to serve as effective mudsnail contact deterrents across a range of water temperatures (8, 12, 18, and 24° C), hardness (75, 125, 175, and 300 mg/L as CaCO3), pH (6, 7, and 8.5), fouling (0, 6, and 10 weeks of exposure), and water velocities (0, 9, and 33 cm/s). Each of these factors was evaluated in a sequential set of separate experiments conducted at the Colorado State University Foothills Fisheries Laboratory during 2009-10. Mean crawling distance (MCD) of the mudsnails in the temperature, hardness, and pH experiments was significantly lower on the SC and MC surface treatment compared to the NP treatment (p < 0.05). Additionally, maximum observed crawling distance (CDmax) was also consistently lower on the SC (1139 mm), MC (672 mm), and AP (1509 mm) treatments versus the NP (1969 mm) treatment. The NP treatment was the only surface where MCD was significantly affected by all three physicochemical parameters (p > 0.05). In the fouling experiment, MCD increased significantly on the AP surface treatment after exposure to fouling from 353 ± 83 mm (mean ± SE) at week 0 to 1207 ± 196 at week 6; no significant increase in this parameter was found on either solid copper surface. Finally, in the water velocity experiment, overall MCD on the copper surfaces was significantly lower in the 0 cm/s velocity treatment (30 ± 6.3 mm) compared to either 9 cm/s (302 ± 47.4 mm) or 33 cm/s (278 ± 50.2 mm). Under flowing water conditions, MC was the most effective treatment for limiting the MCD and CDmax of the mudsnails. Finally, there was no evidence to suggest that at the levels tested, velocity alone could serve as a deterrent to mudsnails. Overall, MC and SC were the most effective surfaces in terms of limiting the locomotor activity of the mudsnail. We recommend that barriers constructed of either of these materials be a minimum of 250 cm to provide a satisfactory level of protection against mudsnail invasion. Additional considerations including design and integration with other types of barriers are discussed.